Tolerância a Phytophthora cinnamomi de portaenxertos de abacateiro e propagação in vitro - Gutierrez Rodriguez, Edwin Antonio [UNESP] (2016)
The tests in this study aimed to approach the answer to the question : The progeny of avocado tolerant rootstocks keeps the tolerance to to Phytophthora cinnamomi. Moreover aimed at addressing issues related to the in vitro establishment of explants of Duke 7 and Toro canyon cultivars.